Evaluasi Kesuksesan Sistem Informasi Model Delone & McLean pada Sistem Informasi Manajemen Daerah Barang Milik Daerah - Tasha Ulfah Haura; Sulistia Suwondo; Ira Novianty (Indonesian Accounting Research Journal, 2021)
To evaluate information systems successfulness of SIMDA BMD in Bandung Regency Government using Delone & Mclean Model (2003) is the research aims. Research type is quantitative descriptive. Samples are 33 SKPD determined by purposive sampling approach with 66 respondents which are goods handler. Primary also secondary data are the source of data comes from. The data analysis method used is SEM-PLS with SmartPLS 3.3.2 software. The results show that the quality of the system and service quality is verified not to affect user satisfaction, while the quality of information is proven to affect user satisfaction. User satisfaction is verified to affect the net benefits of SIMDA BMD. The conclution is the implementation of SIMDA BMD in Bandung Regency Government can be classified as successful.